Severe necroziting vasculitis in a patient with hepatitis C virus infection treated by interferon - Pateron, Dominique; FAIN, Olivier; Sehonou, Jean Jacques; Trinchet, JC; Beaugrand, M (My University, 1996)
Pateron D, Fain O, Sehonnou J, Trinchet JC, Beaugrand M. . . 1996 Jan-Feb; 14 (1): 79-81.